CTIM-31. USE OF A SINGLE PEPTIDE CHECKPOINT INHIBITOR FOR TREATMENT OF CENTRAL NERVOUS SYSTEM TUMORS. (9th November 2020) - Moertel, Christopher; Xiong, Zhengming; Zellmer, David; Pluhar, Elizabeth; Neil, Elizabeth; Greengard, Emely; Olin, Michael
Abstract: Cancer immunotherapy has revolutionized clinical management of malignancies by generating long-term, durable control of tumors. Unfortunately, these therapies often cause serious immune-related adverse events. In addition, only a small percentage of solid tumors respond to these therapies and there is little efficacy in CNS tumors. Our research is focused on the CD200 immune checkpoint, which modulates the immune system through the inhibitory receptor (CD200R1) and activation receptors (CD200AR). We demonstrated that targeting the CD200AR with a checkpoint peptide ligand (CD200AR-L) activates the immune system and renders it impervious to the inhibitory effects of CD200. In a pre-clinical canine spontaneous high-grade glioma trial, CD200AR-L, with autologous tumor lysate vaccination, resulted in a 20% two-year progression-free survival; no toxicities or adverse effects were observed. We suggest this result was due to the ability of the CD200AR-L to modulate multiple immune checkpoints. During the characterization of the CD200AR-L, we discovered signaling molecules are shared by the CD200 and PD-1/PD-L1 checkpoint pathways, suggesting these immune checkpoints are connected. Our preliminary studies demonstrated that the inhibitory CD200R1 and PD-1 mediate immune checkpoint signaling activities through the SHIP1/2. Moreover, CD200AR-L overpowers the suppressive effects of CD200 and PD-L1, which are both shed by tumors, by downregulating the inhibitory CD200R1 and PD-1 on both antigen-presenting cells (APC ) and T-cells. In addition, CD200AR-L downregulates PD-1 on APCs and inhibits the upregulation of PD-L1 and CTLA4. These studies led to the discovery that the novel peptide modulates the CD200, PD-1/PD-L1 and CTLA-4 pathways, providing the basis for the translatable development of a CD200-directed peptide for clinical use against multiple tumors including gliomas. These studies led to FDA approval of this peptide for the first in human phase I single center, open-label, dose-escalation clinical trial in adult and pediatric trial for children with recurrent malignant brain tumors.